Model study of temperature dependent dynamic antiferromagnetic spin susceptibility in graphene. (September 2016) - Sahu, Sivabrata; Gouda, H. S.; Parashar, S. K. S.; Rout, G. C.
Abstract: We report here a microscopic theoretical study of dynamic anti-ferromagnetic spin susceptibility of electrons for graphene systems, which deal with a tight-binding model Hamiltonian consisting of the hopping of electrons up to third nearest-neighbours, impurity and substrate effects besides Coulomb interaction of electrons at A-and B- sub-lattices. The spin susceptibility involves four two-particle Green's functions, which are calculated by Zubarev's Green's function technique. The up and down spin electron occupancies at A and B sub-lattices are computed numerically and self-consistently. The temperature dependent susceptibility becomes smooth for U=uc t1 with critical Coulomb potential uc =2.2, whereas the susceptibility shows more suppression at low temperatures in anti-ferromagnetic phase for u uc . The susceptibility is suppressed due to the increase of external periodic frequency imposed on the system. The A site doping enhances the susceptibility, while the B site doping suppresses it. The increase of the substrate induced gap enhances the susceptibility. The energy dependent real part of susceptibility shows that susceptibility minima shift to higher energies with increase of substrate induced gap.